Strategi Pengembangan Wisata Minat Khusus Arung Jeram Di Sungai Citarum Jawa Barat - Nurul Syamsiah; Yudi Satriadi; Ahmad Fauzul Azhim (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study aims to determine the strength, the weaknesses, the opportunities and the threats in the development of special interest tours for rafting on the Citarum River, and to formulate strategies in developing of potential tourist attractions on the Citarum. The research method is the qualitative research. The source of data in the study is the stakeholders of rafting tourism activities on the Citarum. The data are collected by doing observation and by conducting the structured interviews. The data are analyzed using the SWOT analysis method. Based on the IFAS and EFAS results and based on the position of the SWOT diagram, the rafting tour of the Citarum River is in quadrant II, which means although the Citarum rafting tour faces threats, it has good internal strength.